Scaled-energy based spectrum sensing for multiple antennas cognitive radio - Azage, Michael Dejene; Lee, Chaewoo (KSII Transactions on Internet and Information Systems, 2018)
In this paper, for a spectrum sensing purpose, we heuristically established a test statistic (TS) from a sample covariance matrix (SCM) for multiple antennas based cognitive radio. The TS is formulated as a scaled-energy which is calculated as a sum of scaled diagonal entries of a SCM; each of the diagonal entries of a SCM scaled by corresponding row’s Euclidean norm. On the top of that, by combining theoretical results together with simulation observations, we have approximated a decision threshold of the TS which does not need prior knowledge of noise power and primary user signal. Furthermore, simulation results – which are obtained in a fading environment and in a spatially correlating channel model – show that the proposed method stands effect of noise power mismatch (non-uniform noise power) and has significant performance improvement compared with state-of-the-art test statistics.
Keywords: Decision threshold; Fading environment; Noise power; Non-uniform noise; Performance improvements; Sample covariance matrix; Scaled energy; Spectrum sensing; Cognitive radio; Noise power mismatch; Sample covariance matrix; Scaled energy; Spectrum sensing